2020
DOI: 10.1111/jerd.12573
|View full text |Cite
|
Sign up to set email alerts
|

Autotransplantation of third molars with completely formed roots to replace compromised molars with the computer‐aided rapid prototyping

Abstract: Objective: To describe a method to fabricate donor tooth replica to assist surgeons in preparation of recipient socket during tooth autotransplantation. Materials and Methods: A total of 28 compromised molars in 27 patients were transplanted with third molars using computer-aided rapid prototyping (CARP) technique. Surgery time and extra-alveolar time were documented. Postoperatively, the distance between cervix of transplanted tooth and the alveolar wall was measured. The degree of postoperative pain experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Several published case reports and case series have demonstrated the benefit of RP-assisted tooth autotransplantation [ 6 , 7 , 9 , 11 , 12 , 14 , 15 ]. Most of them are case reports, but 1 is a case–control study analysing RP-assisted autotransplantation in paediatric patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several published case reports and case series have demonstrated the benefit of RP-assisted tooth autotransplantation [ 6 , 7 , 9 , 11 , 12 , 14 , 15 ]. Most of them are case reports, but 1 is a case–control study analysing RP-assisted autotransplantation in paediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a satisfying outcome, efforts must be made to perform minimally traumatic surgical extraction and reduce the extra-alveolar time to more adeptly preserve Hertwig’s epithelial root sheath and pulp vitality [ 16 ]. Xia et al [ 14 ] reported that the average extra-alveolar time of their 28 CARP autotransplantation cases was 2.5 min. Kim et al [ 6 ] reported a total of 182 autotransplantation cases using the CARP technique, with an average extra-alveolar time of 7.58 min.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 displays the 3D technique systems used in previous studies and the results obtained [ 11 , 34 51 ]. Although resin is normally used as printing material for the replicas, some researchers have recently reported the use of titanium or cobalt-chrome alloys to make metallic replicas in order to prevent the development of deformities during the sterilization process [ 34 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…a.) Successful No signs of pathology NR less than 1 min 10 Kim et al [ 50 ] 2019 2 third molars Successful No signs of pathology NR 3 and 5 2–60 Xia et al [ 51 ] 2020 28 third molars Successful No signs of pathology SLA 1 to 5 Average: 2.5 24 Verweij et al [ 34 ] 2020 73 premolars 24 M - 3 others In 2016 98% Successful No signs of pathology DMLS 82% less than 1 min NR o. a. open apex, c. a. closed apex, NR Non-Registered, SLA Stereolithography Apparatus, Polyjet Material Jetting, SLM Selective Laser Melting, DMLS Direct Metal Laser Sintering …”
Section: Discussionmentioning
confidence: 99%
“…With recent advances in 3-dimensional (3D) printing technology in dentistry, the application of computer-aided rapid prototyping (CARP) to create a replica of the donor tooth in ATT has improved outcomes [ 6 , 7 ]. Using the CARP replica tooth to guide surgical preparation can reduce the extra-alveolar time of the viable donor tooth and minimize damage to PDL tissues.…”
Section: Introductionmentioning
confidence: 99%